Total Antioxidant Capacity, Catalase Activity and Salivary Oxidative Parameters in Patients with Temporomandibular Disorders - Neda Omidpanah; Saba Ebrahimi; Asad Vaisi Raygani; Hadi Mozafari; Mansour Rezaei (Tehran University of Medical Sciences, 2020)
Objectives: Temporomandibular disorders (TMD) are characterized by pain or discomfort in the temporomandibular joint, periauricular region, masticatory muscles, and neck on one or both sides. It may also be associated with joint sounds, restricted mandibular movements and mandibular deviation. Oxidative agents may have a deleterious role in the pathogenesis of joint diseases, and oxidative stress can lead to TMD. The aim of this study was to assess the oxidative stress biomarkers in the saliva of TMD patients and healthy controls. Materials and Methods: This case-control study was conducted on 30 patients with TMDs (5 males and 25 females) with a mean age of 30.7±13.2 years, and 30 healthy controls (5 males and 25 females) with a mean age of 29.16±11.2 years. Saliva samples were collected according to the standard protocol and the total antioxidant capacity of the saliva (non-enzymatic), catalase activity, and malondialdehyde (MDA) levels were measured using the ferric reducing ability of plasma, Aebi's method, and high-performance liquid chromatography, respectively. Finally, The MDA levels were analyzed by the Mann-Whitney test. Other quantitative parameters were analyzed by independent t-test.  Results: TMD patients had significantly higher salivary levels of MDA compared to the control group (P=0.001). But there were no significant differences in catalase (P=0.49) and total antioxidant capacity (P=0.22) of TMD patients and healthy controls. Conclusion: It seems that oxidative stress may be involved in the pathogenesis of TMDs.